Compensation for Psychological Damage Caused by Negligence : A Comparative Study - Najem, Zainab; Hassan, Haider Falih Hassan (Journal of Legal Sciences, 2023)
Psychological damage is one of the damages that can be compensated under the fault of negligence in the framework of English law, where the latter intends to include an enumeration of civil errors on the basis of which liability can be determined, and aims under each of these errors to protect a specific interest (for example, defamation protects Among the damage to reputation and inconvenience are the rights contained on the land), and the same is true for the rest of the other errors.Compensation for psychological damage resulting from negligence has raised problems in cases where the psychological injury is "pure", that is, those that are not accompanied by a physical injury, which required subjecting them to special requirements by the English judiciary to succeed in obtaining compensation for the aforementioned damage.